2018
DOI: 10.19173/irrodl.v19i1.3139
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Avatars in Gender Segregated Online Learning Within MOOCs in Saudi Arabia - A Rwaq Case Study

Abstract: <p class="3">In Saudi Arabia, gender-segregation is a known issue within higher education that often deprives female tutors from providing online learning and Massive Open Online Courses (MOOCs). As well, students may not be getting the benefit of their experience and teaching. The purpose of this study is to develop an Avatar tool to represent a female tutor in a MOOC course with the aim of alleviating the issues of a gender-segregated society in online learning. This project will undertake and analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…H. Binsahl et al (Binsahl et al, 2020) claimed that female Saudi international students lacked online search skills, while S. Aldayel (Aldayel, 2020) argued that some sociocultural attitudes minimized the use of technology among female Saudi students. Similarly, R. Adham et al (Adham et al, 2016) reported that the segregated educational system prevented female Saudi students from benefiting from online learning, and they decreased their opportunities to access work. This view was also held by R. Baki (Baki, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…H. Binsahl et al (Binsahl et al, 2020) claimed that female Saudi international students lacked online search skills, while S. Aldayel (Aldayel, 2020) argued that some sociocultural attitudes minimized the use of technology among female Saudi students. Similarly, R. Adham et al (Adham et al, 2016) reported that the segregated educational system prevented female Saudi students from benefiting from online learning, and they decreased their opportunities to access work. This view was also held by R. Baki (Baki, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported that the dominant perspective published by public media was about the role of MOOC in revolutionizing higher education, which was likely to boost the public's acceptance of the changes in existing higher education structures. focused on how technology and artificial intelligence can be used to improve teaching and learning in MOOCs was also documented (Adham et al, 2016;Khalid et al, 2020;Lundqvist et al, 2020).…”
Section: Research On Moocs In New Zealandmentioning
confidence: 99%
“…It is also believed that virtual teaching or immersive education in a country like SA can propel freedom of expression among women. Beyond that, new trends that can also be visible through virtual learning is that it holds potential in blurring social and cultural boundaries, will evoke better social interaction, lower or eradicate the social anxiety for females and considerably remove the gender segregation norms in the country (Adham, Lundqvist & Parslow, 2016). Walker (2013) has affirmed that holography can be a functional tool for learners of all age groups.…”
Section: Women's Benefits From Aou's Initiative Of Virtual Learningmentioning
confidence: 99%